COPYRIGHT PROTECTION OF CINEMATOGRAPHIC WORKS USED IN SONG LYRICS VIDEOS WITHOUT THE CREATOR'S PERMISSION - MUHAMMAD ALGHIFARI AGRAPANA; ENNI SOERJATI PRIOWIRJANTO; TASYA SAFIRANITA RAMLI (Universitas Islam Lamongan, 2021)
ABSTRACTThe use of film works without the author's permission to make a lyric video that aims to promote songs by musicians is a phenomenon that often occurs in the music industry today. This study discusses the extent to which Law Number 28 of 2014 concerning Copyright provides protection in the use of cinematographic works and what legal actions are taken if there is use of cinematographic works without permission. behavior that is appropriate for humans is used as a material for review. The data used is secondary data in the form of an assessment of the literature and laws and regulations related to copyright. The results showed, protection of cinematographic works in Indonesia protects the moral and economic rights of the creator or copyright holder. resolution if there is unauthorized use can be reached through out-of-court dispute resolution, namely alternative dispute resolution and complaints to the Minister for copyrights that are in the digital realm. Settlement of disputes in court in the form of civil lawsuits and criminal charges. The provisions in UUHC regarding this use are still unable to balance the interests of the creator with the community because there is no comprehensive fair use provision. Dispute resolution if there is unauthorized use can be reached through out-of-court dispute resolution, namely alternative dispute resolution and complaints to the Minister for copyrights that are in the digital realm. Settlement of disputes in court in the form of civil lawsuits and criminal charges. The provisions in UUHC regarding this use are still unable to balance the interests of the creator with the community because there is no comprehensive fair use provision. Dispute resolution if there is unauthorized use can be reached through out-of-court dispute resolution, namely alternative dispute resolution and complaints to the Minister for copyrights that are in the digital realm. Settlement of disputes in court in the form of civil lawsuits and criminal charges.